Evaluación de rendimiento y calidad nutricional de arroz biofortificado bajo un sistema de rotación con frijol - Rendon, Natali; Guerrero, Crhistian (2024)
This study evaluated the impact of bean-rice crop rotation on rice yield and nutritional quality under different management treatments in the Zapatero village, Cartagena, Colombia. The experiment, conducted between May 2023 and January 2024, included Caupicor 50 beans and Fedearroz BioZn035 rice. Beans were selected for their nitrogen-fixing capacity and nutritional value, while rice was chosen for its biofortified zinc content and high yield potential. Six treatments were implemented under a randomized complete block design (RCBD) to evaluate parameters such as the number of harvested plants, 100-grain weight, yield, and zinc concentration in the grain. Results showed significant variations among treatments. The organo-mineral treatment achieved the highest yield and the greatest zinc accumulation. Bocashi improved grain weight, while the control treatment recorded the highest number of harvested plants. Soil analysis before and after the rotation showed a decrease in organic matter but improvements in pH, calcium levels, and cation exchange capacity, indicating an increase in soil fertility. These findings confirm that crop rotation with beans and organic amendments improves both soil health and rice productivity, as well as zinc accumulation in the grain. The study highlights the potential of sustainable practices to enhance agricultural productivity and food security in rural areas.